Influence of pollution with sewage water on qualitative and quantitative changes of zooplankton during summer in coastal waters of Lattakia city. (Latakia University Journal -Biological Sciences Series, 2022)
Zooplankton samples were collected from the surface layer of water from three different regions in some of their environmental factors, and from three stations in each region that differ in their distance from the beach.     The sampling process took place in the summer between 17 June 2020 and 23 August 2020, and that was accompanied with measurement of some environmental factors, such as temperatures, which ranged between 25.3°C and 32.4°C, and the biological oxygen demand(BOD5), which were high values and ranged between 2 mg/l and 38 mg/l, and this was accompanied by a decrease in PH values which ranged between 7.25 and 7.67, in addition to a decrease in the concentrations of dissolved oxygen in the water and the values ranged between 2.10 mg/l and 5.40 mg/l, and the salinity during this season was between 34.14 ‰ to 37.75 ‰, as for transparency, the minimum value was 0.4 m and the maximum value was 16.3m, in the study areas as a whole.      145 species and 8 genus of zooplankton have been identified belonging to 24 taxonomic groups, of which 76 species and 2 genes belong to copepod.      It was observed through the study that the abundance of zooplankton decreased in general during the semester, which is summer, as the average total abundance was 3289/m3, and its value was highest in the relatively clean region and reached 3539/m3, while its lowest value was in regions polluted with sewage water and reached 3108/m3 in the second region, and 3220/m3 in the third region.